Otis and Will discover the deep : the record-setting dive of the Bathysphere - Rosenstock, Barb; Roy, Katherine (New York : Little, Brown and Company, 2018)
A biographical account of engineer Otis Barton and naturalist Will Beebe's record-setting descent into the deep ocean in their Bathysphere craft, making the men the first humans to witness deep sea creatures in their natural habitat.
On fold-out pages.
School Library Journal starred, April 2018
Horn Book Starred, March 2018
Bulletin of the Center for Children's Books starre, May 2018
Pub Weekly, April 2018
Booklist, March 2018
Keywords: Underwater exploration -- Juvenile literature; Barton, Otis -- Juvenile literature; Beebe, William, -- 1877-1962 -- Juvenile literature; Underwater exploration; Barton, Otis; Beebe, William, -- 1877-1962.